2018
DOI: 10.3389/fimmu.2018.01463
|View full text |Cite
|
Sign up to set email alerts
|

LPS-Challenged Macrophages Release Microvesicles Coated With Histones

Abstract: Histones are the protein component of nucleosomes, which are the basic packing unit of chromatin. However, histones are also found in the blood, both as components of nucleosomes leaked out from dead cells, or expelled from neutrophils in the active process of NET formation. Circulating histones contribute to inflammation, and to lethality in sepsis, a hyperinflammatory condition, by interacting with specific receptors, notably toll-like receptor 4 (TLR4). Here, we show that histones are also actively released… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 28 publications
(44 reference statements)
2
66
0
Order By: Relevance
“…STED also showed the transfer of HIV-1 from macrophages to astrocytes (Russell et al, 2017). A STORM study showed that the number of histone H2A clusters in the nucleus is decreased in macrophages upon LPS stimulation (Nair et al, 2018), suggesting that histones may be released into the circulation by macrophages and promote distal inflammatory responses.…”
Section: Immune Cells Imaged By Super-resolution Microscopymentioning
confidence: 99%
“…STED also showed the transfer of HIV-1 from macrophages to astrocytes (Russell et al, 2017). A STORM study showed that the number of histone H2A clusters in the nucleus is decreased in macrophages upon LPS stimulation (Nair et al, 2018), suggesting that histones may be released into the circulation by macrophages and promote distal inflammatory responses.…”
Section: Immune Cells Imaged By Super-resolution Microscopymentioning
confidence: 99%
“…Previously, several pathways were shown to lower the protein content during the LPS challenge. Histones were shown to be released into the extracellular medium [49], a general protein secretion via vesicles and exosomes was documented together with protein shedding from the plasma membrane [50], and the association of LPS with receptors driving the production of ROS causing high oxidative stress and degradation of oxidized proteins [51]. While these pathways contribute at a certain unknown degree to the decrease of total protein content upon LPS stimulation, our work provides an aerial view of the total protein fate and points out to the need for a study of mechanisms in CpG DNA induced protein loss in the future.…”
Section: Cpg Dna and Lps Increase The Total Protein Concentration 2hmentioning
confidence: 99%
“…Recent study showed histones are actively released within EVs by LPS‐activated macrophages. And histones are present on the outer surface of vesicles and can interact with TLR4 . Exosome could also transfer mitochondria from airway myeloid‐derived regulatory cells to T cells, and participate in intercellular communication within the airways of human patients with asthma .…”
Section: Biological Functions Of Evsmentioning
confidence: 99%
“…And histones are present on the outer surface of vesicles and can interact with TLR4. 23 Exosome could also transfer mitochondria from airway myeloid-derived regulatory cells to T cells, and participate in intercellular communication within the airways of human patients with asthma. 24 Increased secretion of EV-DNA from senescent cells may contribute to age-related chronic inflammation.…”
Section: Evs and Dampsmentioning
confidence: 99%